The Impact of Foreign Direct Investment and Oil Revenue on Economic Growth in Nigeria - Manasseh , Charles O.; Nwakoby, Ifeoma C.; Okanya, Ogochukwu C.; Ifediora, Chuka U.; Nzidee, Williams A. (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2023)
Many emerging economies, particularly oil-rich countries such as Nigeria, have neglected the key drivers of growth, and consequently resulting in a decline in investment and employment. In the midst of this, the current study sought to examine the extent to which foreign direct investment and oil revenue impact Nigerian economic growth. The estimation was done using ordinary least squares (OLS) techniques, and the Granger causality test was used to determine the direction of causality between FDI, oil revenue, and economic growth using annual time series data from 1991 to 2019. Hence, recognising that annual time series are high-frequency data, all the variables were subjected to OLS assumptions. The empirical findings revealed that FDI and oil revenue significantly impacted growth. Accounting for the impact of economic activities reflected in the role of financial inflow and outflow on economic growth, a significant and positive relationship was found. This implies that international monetary transactions between entities captured in the current account balance are key determinants of growth in Nigeria. Further evidence revealed that variables such as real exchange rate, inflation and interest rates significantly determine economic growth in Nigeria. As such, this finding was further supported by their interactive effects, revealing an inverse and significant influence on economic growth. The Granger causality results show bidirectional causality between oil revenue and growth, as well as between oil revenue and foreign direct investment in Nigeria. The robustness test, which employs GDP per capita and GDP growth as proxies for economic growth, is consistent with empirical evidence. As a result, FDI and oil revenues are important drivers of Nigeria's growth, ceteris paribus.